Nanostructured Lipid Carriers: A Potential Era of Drug Delivery Systems - Chinthaginjala, Haranath; Bogavalli, Varalakshmi; Hindustan, Abdul Ahad; Pathakamuri, Jayasree; Pullaganti, Sai Sree; Gowni, Aswini; Baktha, Bandhavi (Indian Journal of Pharmaceutical Education and Research, 2024)
Nanotechnology is rapidly evolving in the development of new drug delivery systems. Nanostructured lipid carriers are the second era of Solid Lipid Nanoparticles (SLN). These are the alternative carrier system over the solid lipid nanoparticles. Nanostructured lipid carriers are composed of a mixture of solid and liquid lipids, resulting in a solely crystallized lipid system with various advantages over solid lipid nanoparticles, such as higher drug entrapment efficiency, drug release modification versatility, and improved stability. Lipid biocompatibility is responsible for their evolution as a viable drug delivery technology. It was observed that it had superior qualities to other lipid compositions. Various drug-distribution technologies have arisen in the last few decades, with the improvement of nanoscale drug-delivery devices being a fascinating component of this. This review explains the nanostructured lipid carriers in terms of structure, fabrication methods, characterization, future developments, wide applications, patents, and benefits over first-generation lipid nanoparticles. The review is primarily concerned with the forthcoming view of nanostructured lipid carriers and their specificity for various physiological affinities. Several polymers have been used in the development of nanoparticles for drug delivery research to maximize medicinal effectiveness while limiting negative effects. Because of their biological non-toxicity, non-immunogenicity, and compatibility, nanostructured lipid carriers will be the most intensively studied lipid nanocarrier systems
Keywords: Nanostructured lipid carriers; Nanotechnology; Biocompatibility; Lipid nanocarriers